WE CAN OVERCOME IT TOGETHER! A REVIEW ON THE CONCEPT OF FAMILY STRESS - Ergin, Büşra (International Online Journal of Education and Teaching, 2024)
The aim of the study is to examine the postgraduate studies on the concept of ‘family stress’ in the ‘YÖK National Thesis Centre’ database. In the study, in which purposeful sampling was made in line with certain criteria, 51 data sources were reached. Descriptive content analysis of the theses was carried out in the study, which was qualitative in design and data sources were examined by document analysis method. Analysis forms developed by the researcher were used for the analyses. As a result of the study, it was determined that the first study on the concept was in 2002 and the most studies were conducted in 2022-2023. It was determined that the number of master's theses on the concept was higher than the number of doctoral theses. It is observed that the fields that produce the most theses on the concept are psychology and education. It was concluded that the most recurring keywords in the index information of the theses were family, parent, stress and support. The results obtained in the study contribute as an original study in terms of approaching family stress from an interdisciplinary perspective and contributing to the production of effective solutions by considering social benefit.